Multiple Klebsiella pneumoniae KPC Clones Contribute to an Extended Hospital Outbreak - Ferrari, Carolina; Corbella, Marta; Gaiarsa, Stefano; Comandatore, Francesco; Scaltriti, Erika; Bandi, Claudio; Cambieri, Patrizia; Marone, Piero; Sassera, Davide (Frontiers in Microbiology, 2019)
The circulation of carbapenem-resistant Klebsiella pneumoniae (CRKP) is a significant problem worldwide. In this work we characterize the isolates and reconstruct the spread of a multi-clone epidemic event that occurred in an Intensive Care Unit in a hospital in Northern Italy. The event took place from August 2015 to May 2016 and involved 23 patients. Twelve of these patients were colonized by CRKP at the gastrointestinal level, while the other 11 were infected in various body districts. We retrospectively collected data on the inpatients and characterized a subset of the CRKP isolates using antibiotic resistance profiling and whole genome sequencing. A SNP-based phylogenetic approach was used to depict the evolutionary context of the obtained genomes, showing that 26 of the 32 isolates belong to three genome clusters, while the remaining six were classified as sporadic. The first genome cluster was composed of multi-resistant isolates of Sequence Type (ST) 512. Among those, two were resistant to colistin, one of which indicating the insurgence of resistance during an infection. One patient hospitalized in this period was colonized by two strains of CRKP, both carrying the blaKPC gene (variant KPC-3). The analysis of the genome contig containing the blaKPC locus indicates that the gene was not transmitted between the two isolates. The second infection cluster comprised four other genomes of ST512, while the third one (ST258) colonized 12 patients, causing five clinical infections and resulting in seven deaths. This cluster presented the highest level of antibiotic resistance, including colistin resistance in all 17 analysed isolates. The three outbreaking clones did not present more virulence genes than the sporadic isolates and had different patterns of antibiotic resistance, however were clearly distinct from the sporadic ones in terms of infection status, being the only ones causing overt infections.